CHONDROGENIC DIFFERENTIATION OF ADIPOSE-DERIVED MESENCHYMAL STEM CELLS INDUCED BY L-ASCORBIC ACID AND PLATELET RICH PLASMA ON SILK FIBROIN SCAFFOLD - MAJEDA ALFARAFISA , NAYLA
Articular cartilage is a thin connective tissue covering diarthrodial joint surfaces. Unlike other connective tissue, articular cartilage has avascular structure. When articular cartilage experiences trauma or damage from illnes or accident, it tends to develop into degenerative injury. Cartilage tissue engineering may provide alternative solution to replace the function of damaged cartilage. The aim of this reserach was to direct the differentiation of AdiposeDerived Mesenchymal Stem Cells (ADSC) into cartilage tissue using medium containing Platelet Rich Plasma and L-Ascorbic Acid on scaffold made from silk fibroin. This research conducting optimization of three main parameters of tissue engineering: cell, biomaterial scaffold, and bioactive factor. Adipose-Derived Mesenchymal Stem Cells (ADSC) were used as cell source which was characterized to define Mesenchymal Stem Cells. Characterization included plastic adherence, specific surface antigen expression analysis by FACS method, and multipotent differentiation potential by specific extracellular matrix staining. Biomaterial scaffold was made from silk fibrioin by salt leaching method. Biocompatibility and cytotoxicity analysis with MTT assay were conducted to optimize silk fibroin concentration and pore size of the scaffold. On the other hand, L-Ascorbic Acid (LAA) and Platelet Rich Plasma (PRP) were choosen as bioactive factor to induce ADSC differentiation into chondrocyte. Optimization of LAA dan PRP concentration including proliferation and chondrogenic differentiation potential analysis. Chondrogenesis evaluation was performed by measuring the absorbance of chondrocyte specific extracellular matrix glycosaminoglycan (GAG) with Alcian Blue staining at 605nm wavelength. ADSC characterization showed that cells had plastic adherence properties, could express specific surface antigen (CD73, CD90, and CD105), and had the ability to differentiate into three different kind of cells (osteoblast, adipocyte, and chondroblast). Scaffold biocompatibility and cytotoxicity analysis showed that scaffold with 12% w/v silk fibroin concentration and 500µm pore size gave the best cell’s growth curve. Proliferation and chondrogenic differentiation potential analysis showed that 50µg concentration of LAA and 10% concentration of PRP gave the best proliferation rate and chondrogenic differentiation potential. ADSC that has been characterized were seeded on scaffold with 12% w/v silk fibroin concentration and 500µm pore size. Later it was cultured at 50µg LAA and 10% PRP induction medium for 7, 14 and 21 day. Chondrogenesis evaluation showed that GAG content from ADSC seeded on scaffold with12% w/v silk fibroin concentration and 500µm pore size and cultured at 50µg LAA and 10% PRP induction medium continues to increase in each day of observation. Based on this result, it can be concluded ADSC on scaffold with 12% w/v silk fibroin concentration and 500µm pore size differentiation could be directed to grow into chondrocyte using a growth medium containing 50µg LAA and 10% PRP.